Beginning Silverlight 4 in CSharp - Lair, Robert (Apress, 2012)
There are many ways to learn a new technology such as Silverlight. For starters, Microsoft has gotten better and better with the documentation it releases with its programming technologies, and employee blogs and technology sites such as http://www.silverlight.net help by supplementing that documentation. Moreover, you can get information at a number of widely used forums where many experts participate, and, of course, you can always purchase training if you have the cash flow to justify it. While all of these are great options, many people still like to purchase a book on the technology. But with so many books on the market, how do you know which is best? My own philosophy about learning a new technology is that there is no better way than to actually try it out for yourself. That’s why I wrote Beginning Silverlight 4 in C# as a number of step-by-step, walkthrough tutorials that give you hands-on experience with the different topics and get you started developing Silverlight applications on your own.